Understanding soil loss in Mollisol permanent gully head cuts through hydrological and hydromechanical responses - C. Ma; S. Wang; D. Zheng; Y. Zhang; J. Tang; Y. Wen; J. Dong (Hydrology and Earth System Sciences)
During permanent gully development, soil losses on steep slopes and in channel beds are primarily driven by the hydromechanical response and water storage within the soil mass. However, this aspect has been largely overlooked in previous studies on gully erosion in the Mollisol region of northeast China. In this study, erosion intensities during the 111 d of the rainy season and the 97 d of the snow-melting season were analyzed in relation to soil water storage, drainage capacity, and soil suction stress. This analysis was supported by monitoring soil moisture, temperature, and precipitation, as well as experimental investigations of soil hydromechanical properties. Under the same confining stress, Mollisols at the interrupted head cut of Gully no. II exhibited a more rapid increase and more effective dissipation of pore water pressure compared to those at the uninterrupted head cut of Gully no. I. The combination of the soil water characteristic curve and the hydraulic conductivity function revealed that the Mollisols in Gully no. II had a lower air-entry pressure and higher saturated hydraulic conductivity during wetting and drying cycles than those in Gully no. I. The head cut area of Gully no. II demonstrated a rapid water infiltration and drainage response coupled with high soil water storage capacity. The absolute suction stresses within the Mollisols of Gully no. II were lower than those in Gully no. I, potentially leading to greater erosion per unit of steep slope area. Notably, gravitational mass wasting on steep slopes was closely associated with soil suction stress, and a correlation was observed between erosion per unit in the gully bed area and soil water storage. Therefore, predicting soil loss in permanent gullies requires more emphasis on soil water storage and the hydromechanical response of the soil mass rather than solely on rainfall amounts. Specifically, considering the required water storage capacity to generate runoff intensity and reduce suction stress may enable more accurate predictions of soil loss at the permanent gully head cut.